Contrast‐Enhanced Ultrasound in Extracorporeal Support: In Vitro Studies and Initial Experience and Safety Data in the Extreme Premature Fetal Lamb Maintained by the Extrauterine Environment for Neonatal Development. (17th December 2018) - Didier, Ryne A.; Sridharan, Anush; Lawrence, Kendall; Coleman, Beverly G.; Davey, Marcus G.; Flake, Alan W.
Abstract : Objectives: To evaluate the effects of ultrasound contrast agent (UCA) administration on hemodynamic parameters and support equipment in in vitro and in vivo models of extracorporeal support. Methods: In vitro, incrementally increasing bolus doses of a UCA were administered proximal to a membrane oxygenator, and ultrasound cine clips were obtained. The rates of microbubble destruction across the oxygenator and over time were calculated from time‐intensity‐curves. Measurements across the membrane oxygenator were recorded and compared by a repeated‐measures analysis of variance. In vivo, 7 premature fetal lambs were transferred from placental support to the extrauterine environment for neonatal development. Contrast agent boluses were administered for contrast‐enhanced ultrasound (CEUS) examinations. Hemodynamic parameters and serum laboratory values were evaluated before and after the examinations by paired t tests. For oxygenator staining, oxygenator membranes from the in vitro circuit, study animals (n = 4), and control animals (n = 4) were stained for the adherent UCA. Results: In vitro, with all doses (0.1–4 mL), there was no difference in measured parameters across the oxygenator ( P  ≥ .09). Contrast agent destruction (3%–14%) across the oxygenator was observed at the first pass with a progressive decline in contrast intensity over time. In vivo, there was no difference in hemodynamic parameters or serum laboratory values ( P  ≥ .08) with any CEUS examination (n = 17). For oxygenator staining, all oxygenator membranes were negative for UCA with lipid staining. Conclusions: The UCA had no detectable effect on the oxygenator or measured parameters in in vitro and in vivo studies, thus providing additional safety data to support the use of CEUS in the setting of extracorporeal support.